Pengaruh Electronic Word Of Mouth, Hedonic Shopping dan Impluse Buying dan Costumer Statifaction (Survei Pada Konsumen Shoppe Pada Pembelian Produk Scarlett di Desa Tutur ): - Nafiatul Islamiyah; Any Urwatul Wusko (ATRABIS Jurnal Administrasi Bisnis (e-Journal), 2023)
With the increasing number of internet users, a place has emerged for business people to develop their products in the world of e-commerce, one of which is the online store Shopee. The purpose of this study was to find out how much influence Electronic Word Of Mouth (X1) and Hedonic Shopping (X2) have on Impulse Buying (Y1) and Customer Satisfaction (Y2). This study uses an explanatory research approach with quantitative methods. The data collection for this research was by distributing questionnaires to 100 respondents. The data analysis technique uses PLS software, where the data will be processed, described, and discussed to answer and prove the proposed hypothesis. The results of the study are as follows: 1. Electronic Word Of Mouth has a significant and positive influence on Customer Satisfaction variables 2. Electronic Word Of Mouth has a positive and significant infl Dengan semakin banyaknya penggulna internet, mulncull tempat bagi para pelakul bisnis ulntulk mengembangkan produlknya di dulnia e-commerce, salah satulnya adalah toko online Shopee. Tuljulan penelitian ini adalah ulntulk mengetahuli seberapa besar Pengarulh Electronic Word Of Moulth (X1) dan Hedonic Shopping ( X2) Terhadap Impullse Bulying (Y1) dan Costulmer Satisfaction (Y2). Penelitian ini menggulnakan pendekatan explanatory research dengan metode kulantitatif. Pengulmpullan data penelitian ini adalah melaluli sebar kulesioner ataul angket kepada 100 responden. Teknik analisis data menggulnakan software PLS, yang mana data tersebult akan diolah, diulraikan, dan dibahas ulntulk menjawab dan membulktikan hippoptesis yang diajulkan. Adapuln hasil penelitian sebagai berikult: 1. Electronic Word Of Moulth memiliki pengarulh signifikan dan positif terhadap variabel Costulmer Satisfaction 2. Electronic Word Of Moulth memiliki pengarulh positif dan signifikan terhadap implulse bulying, 3. Hedonic Shopping berpengarulh positif dan signifikan terhadap Costulmer Satisfaction, 4. Hedonic Shopping berpengarulh positif dan signifikan terhadap implulse bulying, 5. Implulse bulying memiliki pengarulh positif dan signifikan terhadap Costulmer Satisfaction. uence on impulse buying, 3. Hedonic Shopping has a positive and significant effect on Customer Satisfaction, 4. Hedonic Shopping has a positive and significant effect on impulse buying, 5. Impulse buying has a positive and significant effect on Customer Satisfaction.